Evasão escolar e permanência no Programa Nacional de Acesso ao Ensino Técnico e Emprego: um enfoque a partir da gestão dos processos de aprendizagem organizacional - Carneiro Dias, Marcilio (2015)
This study was based on references that deal with the historical context of Professional Education (MANFREDI, 2002) and Professional Qualification in Brazil (PRESTES and OLOPADE, 2009) placing the National Program for Access to Technical Education and Employment (PRONATEC) in this scenario; of issues related to school dropout and to permanence (DORE et al., 2014), as well as the processes of organizational learning (SILVA, 2009) related to educational management (CASTRO, 2007). The theme proposed has been chosen for the personal and professional interest of the researcher to understand with a more systemic look, the organizational learning processes and their developments in strategies that aim at guaranteeing the permanence and the fight against school dropout. This work aimed at analyzing the educational management strategies articulated by the team manager of PRONATEC at IFPB in João Pessoa Campus, departing from the organizational learning processes related to issues of school dropout and permanence as part of initial and continuing training courses. The research isa descriptive and exploratory methodological procedure of quantitative and qualitative nature. Data collection was carried out through bibliographical research, questionnaire and semi-structured interviews, the last two having been applied to 02 (two) coordinators and 13 (thirteen) supervisors of the Program. In order to interpretthe results, the technique of content analysis has been used. After the interpretations, it has been noticed that from the point of view of all the respondents, the dropouts exist primarily due to external factors and that the internal factors of the João Pessoa Campus have strengthened students permanence. With regards to learning, the individual and group levels were highly emphasized by respondents, featuring the categories of information search, observation, discussion and socialization; in relation to the organizational level it was detected a slight perception of effectiveness; however, interorganizational learning emerged more evidently in the speeches of the coordinators. By fostering the analysis of educational management strategies related to school evasion and permanence, it has been concluded that the team, by means of the learning acquired, developed practices that greatly contributed to improving the panorama of school dropout and permanence over the investigated period and that there is an emerging need to improve the links between the four levels of learning.With this research, it is expected to contribute for the management of the program to understand the relevance of the structuring of the learning processes, in order to map out strategies that provide better quantitative results, especially qualitative, mainly related to school permanence.